An Anthology of London in Literature, 1558–1914 - Hiller, Geoffrey G.; Groves, Peter L.; Dilnot, Alan F. (Springer, 2019)
This anthology brings together extracts from some of the finest writing in English on the subject of that ancient and fascinating city, chosen from the period in which the London we now know was mainly created: the three-anda- half centuries that separate the accession of Elizabeth I from the onset of the First World War, which transformed it from a large town still intimately connected to the neighbouring countryside to the sprawling metropolis of an empire that covered a quarter of the globe. London has always been more than a place to live and work: always the cultural heart of England, for example, and always larger by at least an order of magnitude than any other city in Britain—indeed, for much of this period the largest city in the world. But beyond this, London is a city of the mind, an imaginary space haunted by the great mythopoeic cities of Western culture: Rome, Athens, Babylon, Jerusalem. This is why it has kindled the imagination of some of the greatest writers of English, and why it forms the subject of this anthology. The 142 extracts, which are in all but one case in modernised spelling and punctuation (though including traditional punctuational aids to scansion), are annotated (simple one-word glosses are incorporated into the text in square brackets) and grouped into four sections by historical period, being numbered within those sections: cross-references will take the form “[2.14]” or “(see [4.27])”. Each extract has a brief head-note, and references to the head-note of an extract are indicated by “HN”. References to footnotes will take the form “(see [2.20], n.107)”.